Analysis of shear size effect and failure characteristics of cover interface considering normal force - Sun, Miaojun; Zhang, Zuguo; Deng, Yingying; Du, Cheng; Hu, Gaojian; Liu, Guangjian (Frontiers in Earth Science, 2025)
The shear mechanical properties of the cover interface play a key role in the stability analysis of tunnel surrounding rock structure. To further reveal the coupling effect of overlying stress and size effect on the shear strength and failure mode of the cover interface, this paper adopts the RFPA numerical simulation method to carry out direct shear simulation and normalization analysis of the cover interface under different normal stresses and interface sizes. The results show that the shear strength of the cover interface decreases significantly with the increase of interface size, exhibiting a negative exponential relationship. Normal stress enhances interfacial friction, increases peak and residual shear strength, and has an exponential relationship with the size effect coefficient. The larger the normal stress, the faster the attenuation of size effect. At different sizes, the end effect is significant in small samples, with cracks densely distributed at the ends; Cracks penetrate along the interface in large samples, and residual shear slip is more complete. Based on the normalized shear strength curve, the universality of size effect and the coupling effect of normal stress were revealed. The research results can provide theoretical support and parameter basis for the analysis of shear stability of weak surfaces in underground structures.